Clock routing using binary particle swarm optimization (BPSO) [electronic resource] - Voon, Wee Sun, 1988- , author (2011)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik - Elektronik)) - Universiti Teknologi Malaysia, 2011